2017
DOI: 10.1177/0962280217723945
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating disease prediction models using a cohort whose covariate distribution differs from that of the target population

Abstract: Personal predictive models for disease development play important roles in chronic disease prevention. The performance of these models is evaluated by applying them to the baseline covariates of participants in external cohort studies, with model predictions compared to subjects’ subsequent disease incidence. However the covariate distribution among participants in a validation cohort may differ from that of the population for which the model will be used. Since estimates of predictive model performance depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…We show that weighting the validation sample to better resemble the intervention study can help reduce such biases, and improve upon the transportability of measurement error parameters estimated in an external sample. Previous work has demonstrated similar benefits of implementing propensity score-type weighting methods when using external validation data to adjust for missing confounders 36 and when evaluating disease prediction models in samples that differ from the target population 37 Through our simulation study, we highlighted that under extreme scenarios, it may still be inappropriate to transport if the validation sample is vastly different from the trial on a set of observed characteristics. It is also important to remember that while researchers are often concerned about measurement error, it will only lead to a biased ATE estimate when the outcome error is differential with respect to treatment and the error means are thereby different across treatment groups.…”
Section: Discussionmentioning
confidence: 87%
“…We show that weighting the validation sample to better resemble the intervention study can help reduce such biases, and improve upon the transportability of measurement error parameters estimated in an external sample. Previous work has demonstrated similar benefits of implementing propensity score-type weighting methods when using external validation data to adjust for missing confounders 36 and when evaluating disease prediction models in samples that differ from the target population 37 Through our simulation study, we highlighted that under extreme scenarios, it may still be inappropriate to transport if the validation sample is vastly different from the trial on a set of observed characteristics. It is also important to remember that while researchers are often concerned about measurement error, it will only lead to a biased ATE estimate when the outcome error is differential with respect to treatment and the error means are thereby different across treatment groups.…”
Section: Discussionmentioning
confidence: 87%
“…In this approach, patients who experienced an event after the prediction time frame were considered non-events. The second approach we applied used all patients, and those who did not have complete follow-up for the prediction horizon contributed data only up to the length of time that they were followed, such that competing events are not excluded from the validation sample, but rather censored at their last follow-up time [ 28 ]. We used the rmap package in R for this latter approach.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, features can be analysed in order to identify those which are more robust to common sources of image noise. However, despite the fact that empirical investigations which rely on external validation are deemed to be qualitative better than others by the TRIPOD guidelines [19], this approach can not guarantee the reproducibility of the observed results in every set [20].…”
Section: Introductionmentioning
confidence: 99%